Let's Read Together": A Balanced Computer Assisted Intervention Program and Its Effect on Comprehension amongst at Linguistic Risk Arab First Graders - Makhoul, Baha; Olshtain, Elite; Ibrahim, Raphiq (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The current study investigated the effectiveness of an early balanced computer-assisted intervention program in promoting comprehension skills among Arabic-speaking first graders from disadvantaged socio-economic background, when taking into account the interplay between risk factors impacting Arabic reading acquisition: Arabic language complexity, poor literacy skills and the cognitive and emotional challenges when commencing formal schooling. Forty at literacy-risk Arab first graders were randomly assigned to either the intervention or a comparison group, each including 20 children. A qualified tutor was assigned to each participants in the intervention group. To assess the childrens progress in the intervention group, measurements were carried across three different periods during the implementation of the program. In addition, comprehension assessments were administrated to both groups prior and after the program commencement and completion, respectively. The intervention group showed greater progress in comprehension skills and vocabulary when compared to the comparison group in all the measurements. The obtained results stress the necessity for early balanced intervention in order to close the gaps in comprehension skills among at-risk children.